2020
DOI: 10.1007/s11307-020-01514-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Characterization of Four 18F-Labeled S1PR1 Tracers for Neuroinflammation

Abstract: Purpose:The sphingosine-1-phosphate receptor 1 (S1PR1) is an important biomarker for imaging inflammation in the central nervous system (CNS). Herein we report our recent evaluation of four 18 F-labeled S1PR1 tracers ( 18 F-TZ43113, 18 F-TZ35104, 18 F-TZ4877, and 18 F-TZ4881) in a rat model of multiple sclerosis (MS).Procedures: MicroPET studies of each tracer's uptake and kinetics were performed in the experimental autoimmune encephalomyelitis (EAE) rat model of MS to quantify upregulated S1PR1 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Beyond, it has been shown that S1Pr expression levels dynamically change during the formation of inflammatory lesion in MS, such as increased S1Pr1 and S1Pr3 expression levels on reactive astrocytes in active and chronic inactive MS lesions [104], indicating that astrocytes may act as target of fingolimod and siponimod within the CNS. Induced S1Pr expression levels have as well been reported in the EAE model [105][106][107]. Interestingly, it has been suggested that overexpression of the S1Pr1 on reactive astrocytes drives the neuropathology of the MS rebound after fingolimod discontinuation [108].…”
Section: Sphingosine-1 Phosphate Signalingmentioning
confidence: 71%
See 1 more Smart Citation
“…Beyond, it has been shown that S1Pr expression levels dynamically change during the formation of inflammatory lesion in MS, such as increased S1Pr1 and S1Pr3 expression levels on reactive astrocytes in active and chronic inactive MS lesions [104], indicating that astrocytes may act as target of fingolimod and siponimod within the CNS. Induced S1Pr expression levels have as well been reported in the EAE model [105][106][107]. Interestingly, it has been suggested that overexpression of the S1Pr1 on reactive astrocytes drives the neuropathology of the MS rebound after fingolimod discontinuation [108].…”
Section: Sphingosine-1 Phosphate Signalingmentioning
confidence: 71%
“…Cells 2020, 9, x FOR PEER REVIEW 7 of 17 siponimod within the CNS. Induced S1Pr expression levels have as well been reported in the EAE model [105][106][107]. Interestingly, it has been suggested that overexpression of the S1Pr1 on reactive astrocytes drives the neuropathology of the MS rebound after fingolimod discontinuation [108].…”
Section: From Fty720 To Siponimodmentioning
confidence: 71%
“…These results have important implications for the future schizophrenia subtype-based studies with in vivo PET S1PR1. The S1PR1 has recently emerged as a promising radiotracer for in vivo PET imaging (Liu et al, 2017; Liu et al, 2016; Liu et al, 2020; Luo et al, 2019). The S1PR1 protein upregulation only in Type 2 demonstrated in this study was in line with previous reports on the S1PR1 mRNA upregulation only in Type 2 schizophrenia patients (Bowen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A serious limitation of mRNA expression studies like that of Bowen et al (Bowen et al, 2019) is that they require brain tissue which is generally not available except at autopsy. Fortunately PET ligands for one of the genes differentially expressed in the Type 2 schizophrenic brains, sphingosine-1-phosphate receptor-1 (S1PR1) have been developed in the Mallinckrodt Institute of Radiology, Washington University in St. Louis (Jin et al, 2017; Liu et al, 2017; Liu et al, 2016; Liu et al, 2020; Luo et al, 2019). The present study examines the differential expression of S1PR1 in the DLPFC of Type 1 and Type 2 schizophrenic patients at the protein level as a preliminary step towards the use of PET to distinguish Type 1 from Type 2 schizophrenia during life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation